2017
DOI: 10.1038/npp.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: A Single Dose, Randomized, Controlled Proof-Of-Mechanism Study of a Novel Vasopressin 1a Receptor Antagonist (RG7713) in High-Functioning Adults with Autism Spectrum Disorder

Abstract: In this paper, page 4: Table 1, Vineland II Adaptive Behavior score is a title; therefore the score '62 (12.9)' should be removed. In the second paragraph of the RESULTS section, the VABS-II score should be '63 (12.5)' instead of '62 (12.9)'. Page 6: Table 2, the WAVW (ratio) section, Eyes p-value should be '0.99,' instead of '0.10'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…This study did not involve an intervention, and therefore the responsiveness to change of the features that discriminate between the ASD and TD groups could not be assessed, and this is a next step for an ongoing intervention study (NCT03664232). However, unlike Umbricht et al ( 2017 ) who determined that first orientation to biological motion was less in an ASD group, and increased following vasopressin 1a receptor antagonist administration, we did not find evidence of between-group differences for this feature. Future studies are required to determine whether attention to biological motion can be increased in response to intervention, and whether this could be a precursor to other observable change in social interaction.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study did not involve an intervention, and therefore the responsiveness to change of the features that discriminate between the ASD and TD groups could not be assessed, and this is a next step for an ongoing intervention study (NCT03664232). However, unlike Umbricht et al ( 2017 ) who determined that first orientation to biological motion was less in an ASD group, and increased following vasopressin 1a receptor antagonist administration, we did not find evidence of between-group differences for this feature. Future studies are required to determine whether attention to biological motion can be increased in response to intervention, and whether this could be a precursor to other observable change in social interaction.…”
Section: Discussioncontrasting
confidence: 99%
“…A PLD representing biological motion was shown on one side and a non-biological PLD was shown on the other. These stimuli were previously used by and reported by Umbricht et al ( 2017 ). The PLDs were made up of dynamic black-point displays on a grey background (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, pharmacological therapy for ASD has not focused on the core symptoms but mainly on the associated symptoms of the disease. Recent studies revealed that V 1A receptor antagonists can regulate the effect of the AVP hormone and thus influence the core symptoms of autism. , …”
mentioning
confidence: 99%
“…PF-184563 ( 1 ) was originally developed for the treatment of dysmenorrhea; despite its published benefits, however, the compound did not reach the clinical phase. It was a milestone in the research of V 1A antagonists when Roche demonstrated under clinical circumstances that the inhibition of the V 1A receptor may improve social communication skills in adults with high-functioning ASD. , Their frontrunner compound balovaptan ( 2 ) showed significant efficacy on the Vineland-II scale in ASD; furthermore, Roche initiated a phase 2 study in children and adolescents in 2016. Up to June 2020, the molecule was being tested in Phase 2, then the study was terminated due to ineffectiveness in the studied population…”
mentioning
confidence: 99%